Revolusi Fashion Ramah Lingkungan: Mengubah Limbah Denim Menjadi Tas Teknik Art Embroidery - Rachmandi, Cut Dea; Wahyunigsih, Urip (Hastagina : Jurnal Kriya Seni, 2025)
This research focuses on innovation in sustainable fashion through the transformation of denim waste into bag products using art embroidery techniques. The study is motivated by the increasing amount of textile waste, particularly denim, which is difficult to decompose and poses a threat to the environment. Transforming this waste into high-value and aesthetically appealing products represents a strategic effort to support the sustainable fashion movement. The main objective of this research is to develop eco-friendly bag designs that are not only functional but also have artistic and economic value through the exploration of creative embroidery techniques. The research method involves several stages: collecting used denim materials, designing the product, experimenting with various embroidery patterns and threads, and analyzing the aesthetic and functional aspects of the final product. The creative process applies the principle of upcycling, emphasizing the transformation of discarded materials into new, higher-value products. The results show that denim waste can be processed into durable, visually attractive bags with strong market potential. The application of art embroidery significantly enhances the artistic value and unique character of the products. This study contributes to increasing awareness of sustainability within the fashion industry while opening opportunities for recycling-based creative economies. Furthermore, the results can inspire young designers to innovate in creating environmentally friendly products that are aesthetic, functional, and rich in cultural value.